Transformation of non-small cell lung cancer into small cell lung cancer in a patient with advanced lung cancer: a case report. Issue 8 (August 2021) - Yang, Zhengyuan; Lin, Yingcheng; Wang, Hongbiao
Targeted therapy in patients with epidermal growth factor receptor ( EGFR )-mutated non-small cell lung cancer (NSCLC) often fails because of drug resistance. Here, we report a 57-year-old male patient with stage IV small cell lung cancer (SCLC) transformation during targeted therapy. Chest computerized tomography (CT), hematoxylin and eosin histological examination, immunohistochemistry, allele refractory mutation system‐based quantitative polymerase chain reaction analysis of EGFR point mutations, and next-generation sequencing were performed for diagnosis and therapeutic efficacy evaluation. A combination of chest CT, histological examination, and immunohistochemistry confirmed the initial NSCLC diagnosis. Next-generation sequencing detected only EGFR exon 19 deletion ( ex19del ) before treatment and later identified EGFR exon20p.T790M point mutation, EGFR amplification, myc proto-oncogene ( MYC) amplification, retinoblastoma 1 ( RB1) mutation, and tumor protein 53 ( TP53) mutation. Histology and immunohistochemistry revealed transformation from NSCLC to SCLC during treatment, which eventually returned to NSCLC. Drug resistance to targeted therapy for patients with NSCLC frequently occurs because of EGFR exon20p.T790M point mutation, TP53 mutation, RB1 mutation, and MYC amplification. These mutations are also the major determining factors of NSCLC outcomes. Therefore, next-generation sequencing should be performed to confirm drug efficacy during targeted therapy for NSCLC.